Letter to Paul and May Beck Bennet, ca. 1939-1945 - Bennet, Samuel Stevens (Valdosta State University Archives and Special Collections, 1939)
Letter from Samuel Stevens Bennet to his nephew, Paul Hansell Bennet, and wife, May Beck (Mary Rebeca), sharing some of his memories after a recent visit to their house, where he grew up. His recollections include his brothers, Stanley Bennet, Matthew Bennet, and Joseph Bennet, as well as father, William Baker Bennet, and mother, Martha Jane Campbell.
1 electronic record, PDF document and 10 JP2 image scans
Keywords: Brooks County (Ga.); Quitman (Ga.); Georgia; Letters; Family histories; Genealogy